Love in Hegel’s Philosophy - Shabani, Munzer; Mahan, Hania (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with the concept of love in the philosophy of Hegel, in an attempt to highlight this concept in the context of the man’s discovery of both himself and the other , and the trend to be united with the other in terms of that individual’s sense of this unity. Adoration of Hegel is important for marriage, but not enough to hold it. Inclination and desire must be accompanied by conscience, and this requires that there be a will to develop this desire to a contract link which makes the idea of love reach its climax as marriage is considered the continuation of human life. Through marriage the family is formed and grow to form a community with strong links united in light of the dominance of a single power and rule forming the so-called state